Academic Stress Among Nursing Students: Dominant Symptom Dimensions and Implications for Counseling Interventions - Nur Kholiza Fitri; Netrawati Netrawati; Zadrian Ardi; Puji Gusri Handayani (Scidacplus, 2026)
Nursing students are particularly vulnerable to academic stress due to the combined demands of academic coursework and clinical training. This study aimed to describe the academic stress profile of nursing students in Padang, Indonesia, by examining four symptom dimensions: cognitive (thought), behavioral, physical, and emotional (feeling) symptoms. A quantitative descriptive cross-sectional design was employed, involving 104 nursing students selected through total sampling. Data were collected using a self-developed 35-item Academic Stress Questionnaire based on a five-point Likert scale, which demonstrated excellent internal consistency (Cronbach's α = .954). Descriptive statistical analysis showed that most students experienced moderate (34.6%) or high (30.8%) levels of academic stress, with 35.6% classified in the high-to-very-high categories. Among the four symptom dimensions, cognitive (thought) symptoms were the most dominant, followed by emotional (feeling), behavioral, and physical symptoms. These findings indicate that academic stress among nursing students is characterized primarily by cognitive and emotional manifestations rather than physical symptoms. The results provide an empirical basis for developing targeted guidance and counseling interventions, particularly those emphasizing cognitive restructuring and emotional regulation, to better support nursing students' psychological well-being and academic adjustment.